Leukocyte Associated Immunoglobulin Like Receptor 1 Regulation and Function on Monocytes and Dendritic Cells During Inflammation - Carvalheiro, Tiago; Garcia, Samuel; Pascoal Ramos, M. Inês; Giovannone, Barbara; Radstake, Timothy R. D. J.; Marut, Wioleta; Meyaard, Linde (Frontiers in Immunology, 2020)
Inhibitory receptors are crucial immune regulators and are essential to prevent exacerbated responses, thus contributing to immune homeostasis. Leukocyte associated immunoglobulin like receptor 1 (LAIR-1) is an immune inhibitory receptor which has collagen and collagen domain containing proteins as ligands. LAIR-1 is broadly expressed on immune cells and has a large availability of ligands in both circulation and tissues, implicating a need for tight regulation of this interaction. In the current study, we sought to examine the regulation and function of LAIR-1 on monocyte, dendritic cell (DC) and macrophage subtypes, using different in vitro models. We found that LAIR-1 is highly expressed on intermediate monocytes as well as on plasmacytoid DCs. LAIR-1 is also expressed on skin immune cells, mainly on tissue CD14+ cells, macrophages and CD1c+ DCs. In vitro, monocyte and type-2 conventional DC stimulation leads to LAIR-1 upregulation, which may reflect the importance of LAIR-1 as negative regulator under inflammatory conditions. Indeed, we demonstrate that LAIR-1 ligation on monocytes inhibits toll like receptor (TLR)4 and Interferon (IFN)-α- induced signals. Furthermore, LAIR-1 is downregulated on GM-CSF and IFN-γ monocyte-derived macrophages and monocyte-derived DCs. In addition, LAIR-1 triggering during monocyte derived-DC differentiation results in significant phenotypic changes, as well as a different response to TLR4 and IFN-α stimulation. This indicates a role for LAIR-1 in skewing DC function, which impacts the cytokine expression profile of these cells. In conclusion, we demonstrate that LAIR-1 is consistently upregulated on monocytes and DC during the inflammatory phase of the immune response and tends to restore its expression during the resolution phase. Under inflammatory conditions, LAIR-1 has an inhibitory function, pointing towards to a potential intervention opportunity targeting LAIR-1 in inflammatory conditions.